Trifluoromethylthiolation of Diazo Compounds through Copper Carbene Migratory Insertion. Issue 15 (18th March 2014) - Wang, Xi; Zhou, Yujing; Ji, Guojing; Wu, Guojiao; Li, Ming; Zhang, Yan; Wang, Jianbo
Abstract: A strategy to introduce the SCF3 group through the Cu I ‐promoted reaction of diazo compounds with the nucleophilic AgSCF3 trifluoromethylthiolation reagent was developed. Various diazo compounds were smoothly converted under mild conditions to form the C(sp 3 )–SCF3 bond. Mechanistically, migratory insertion of SCF3 ‐bearing Cu carbene intermediates is involved in this transformation. Abstract : A strategy to introduce the SCF3 group through the Cu I ‐promoted reaction of diazo compounds with the nucleophilic AgSCF3 trifluoromethylthiolation reagent is developed. Various diazo compounds are smoothly converted under mild conditions to form the C(sp 3 )–SCF3 bond. Migratory insertion of SCF3 ‐bearing Cu I carbene intermediates is proposed as the key step in this transformation.